Impact of wastewater treatment plant discharges on macroalgae and macrofauna assemblages of the intertidal rocky shore in the southeastern Bay of Biscay. (15th June 2019) - Huguenin, L.; Lalanne, Y.; de Casamajor, M.N.; Gorostiaga, J.M.; Quintano, E.; Salerno, M.; Monperrus, M.
Abstract: Rocky intertidal habitats are particularly vulnerable to anthropogenic pressures especially in areas with high urban concentrations such as southeastern Bay of Biscay. This research aims to establish an assessment of the potential impact of sewage discharges on intertidal rocky benthic assemblages on macroalgae and on macrofauna as required by the European Directives (Water Framework Directive -WFD and Marine Strategy Framework Directive -MSFD). The assemblages were sampled at five locations according to a control-impact design. A moderate detectable effect of discharges was highlighted on the assemblage structure by means of multivariate analyses but this was less evident using other biological and ecological metrics. Results would also suggest that benthic macroalgae constitute for the study area the best relevant biotic component to assess the effect of this pressure on the intertidal rocky platform habitats. Changes in the relative abundance of Ceramium spp., Corallina spp. and Halopteris scoparia were mainly responsible of the dissimilarities found. Finally, a pseudo-ecological quality ratio, based on the current WFD metrics, was also calculated for each site within locations (i.e. each distance from the outfall) to assess its sensitivity to this type of pressure. Results were conformed with those of the WFD monitoring because the un- or less-impacted sites were ranked as " Good" contrary to the others ranked as " Moderate" . Thus, this work provides additional information for the MSFD and bridges deficiencies emphasized by Directives on the response of biological indicators to various pressures and the biocenosis of southeastern Bay of Biscay. Highlights: Detectable effects of discharges were highlighted on assemblage structure. Macroalgae constituted a relevant biotic component to study impact of WWTP discharges. Ceramium spp., Corallina spp. and Halopteris scoparia were mainly responsible of the dissimilarities. The pseudo-EQR ratio was sensitive to the WWTP pressure.